Detecting longitudinal changes in activities of daily living (ADL) dependence: Optimizing ADL staircase response choices. (October 2019) - Axmon, Anna; Ekstam, Lisa; Slaug, Björn; Schmidt, Steven M; Fänge, Agneta Malmgren
Introduction: Using a sum score based on a three-graded response scale for the activities of daily living staircase has previously been found to increase the statistical power compared to dichotomized responses when assessing longitudinal changes in activities of daily living. We aimed to investigate if the statistical power could be further increased by using a four-graded scale. Methods: We used data from two previous studies on community-living people to calculate sum scores based on a dichotomized (independent/dependent), a three-graded (independent/partly dependent/dependent), and a four-graded (independent without difficulty/independent with difficulty/partly dependent/dependent) response scale for the activities of daily living staircase. In total, 1818 paired observations (baseline to follow-up) from 482 people were included. Statistical power was estimated for the entire material as well as stratified by follow-up time and baseline activities of daily living using simulations. Results: The four-graded scale provided the highest statistical power, particularly for shorter follow-up times and low and high baseline activities of daily living, but had similar statistical power to the three-graded scale for longer follow-up times and medium baseline activities of daily living. Conclusion: Adding a second level to "independent" in the activities of daily living staircase improved the detection of changes over time.